Icelandic physiotherapists’ perceptions of contextual factors as triggers of nocebo effects: a mixed methods survey - Snook, Abigail Grover; Waage, Ingvi S; Arnadottir, Solveig A; Bjornsdottir, Sigrun V; Rossettini, Giacomo; Testa, Marco (Physiotherapy theory and practice, 2025)
Contextual factors surrounding physiotherapy treatment can trigger nocebo effects, resulting in negative outcomes despite evidence-based treatment. This study explored Icelandic physiotherapists' awareness, perception, and prevention of contextual factors that may trigger nocebo effects. This was a cross-sectional, convergent mixed-methods study utilizing an online survey. Quantitative data was collected by translating and adapting a previously developed survey and analyzed using descriptive and non-parametric statistics. Qualitative data from open-ended questions were transformed and analyzed using a contextual factor framework. For the quantitative analysis, 206 responses were included. Seventy percent of Icelandic physiotherapists reported "seldom" or "rarely" encountering nocebo effects. The highest-rated perceived causes, based on the percent answering "very much" or "much," were inappropriate touch (89%), lack of trust between physiotherapist and patient (85%), use of negative language by the physiotherapist (83%), patient's prior negative experiences (80%), physiotherapist's negative attitude (78%), patient's negative expectations (77%), and negative non-verbal communication (74%). The most endorsed strategy for preventing nocebo effects was to teach and train patients in coping skills. Eighty-eight percent agreed that nocebo effects should be part of the physiotherapy curriculum. Qualitative descriptions of nocebo effects by 81 physiotherapists showed little self-reflection, with a tendency to attribute nocebo effects primarily to the patient's mind-set. Comparisons to other surveys showed similarities that may be universal among physiotherapists alongside notable differences. Physiotherapists frequently attributed nocebo effects to the patient's mind-set but may need to consider a broader range of contextual factors to reduce nocebo effects more effectively.